PERUBAHAN TINGKAT SUKU BUNGA DAN KINERJA PASAR MODAL INDONESIA: ANALISIS PADA TINGKAT PASAR DAN TINGKAT INDUSTRI - Lantara, I Wayan Nuka (Journal of Indonesian Economy and Business, 2004)
The objective of this paper is to test empirically the performance of Indonesian capitalmarket following the interest rate change. This study also tests the relationship between the interest rate changes and the subsequence performance in various industries, which are financial and manufacture sector. We used market level analysis as well as industry level analysis.We examine the 1996-2001 period. The sample consists of 64 interest rate change, 34increase and 30 decrease. We used one market index and two industry index, which areIndonesian Capital Market Composite Index, Financial Sector Index and ManufactureSector Index.In order to examine the market and industry performance following interest ratechange, we test the mean-adjusted return (MAR) and cumulative mean-adjusted return(CMAR) during 21 event windows with t-test statistics. The results indicate that market and industrial performance react negatively to the increase of interest rate, while reactpositively to the decrease of interest rate. Besides, there is also an indication that financialsector performance tends to be more sensitive than manufacture sector performance.Keywords: Interest rate change, market performance, financial and manufactureperformance, market-level analysis, industry-level analysis.